Assessment of laboratory methods for evaluating cassava genotypes for resistance to root rot disease - Onyeka, T.J.; Dixon, A.; Ekpo, E.J. (Springer, 2005)
Field evaluation of six cassava genotypes for resistance to root rot disease was compared with three rapid laboratory methods (whole root inoculation, root slice inoculation, and stem inoculation) for resistance screening. Both the field evaluation and the three laboratory methods separated the varieties into resistant and susceptible groups. Genotypes 30572 and 91/02324 were resistant while 92/0247, 92/0057 and TME-1 were susceptible. One genotype (30001) was not consistent in its reaction between field evaluation and laboratory assays. In the laboratory assays with three fungal pathogens, different pathogens varied in their levels of virulence on host genotypes. With the most virulent pathogen (Botryodiplodia theobromae), the majority of the genotypes reacted in the same way across trials with the root slice and whole root assays. Due to the good correlation between the whole root assay and the field results, we recommend this for the routine assessment of cassava resistance to root rot disease and for the analysis of virulence of pathogen isolates. However, because of the advantages in terms of economy of labour, space, time, quantity of root and inoculum required, the root slice assay could be used for the preliminary screening of large cassava accessions. The selected genotypes can then be further screened with the whole root inoculation method.